Relations between life satisfaction, family and friendship satisfaction and religiosity in adolescence - Silva, Doralúcia Gil da (2017)
This work aimed to discuss relations between life satisfaction, family and friendship satisfaction and religiosity in a sample of adolescents. A record of sociodemographic data, a Multidimensional Scale of Life Satisfaction and a Positive and Negative Affect Scale were applied in 420 students (M= 14.91 years old; SD=1.65) from public schools of Porto Alegre. The results indicated that adolescents who reported having religion had higher life satisfaction, subjective well-being, and family and friendship satisfaction, all with significant differences. Religiosity and interpersonal relationships are factors that can act in a positive way and increase well-being perception by the adolescent. Implications about the form of to assess subjective well-being, as well as religiosity, are discussed.